Case report: An unusual presentation of puerperal sepsis - Kabiri, Doron; Prus, Diana; Alter, Roie; Gordon, Gali; Porat, Shay; Ezra, Yossef (Frontiers in Medicine, 2022)
Group A Streptococcus (GAS; Streptococcus pyogenes) is a facultative gram-positive coccus, uncommonly colonizing parturient genitalia, where its presence can potentially lead to a life-threatening invasive infection after delivery. GAS infection typically occurs within the first 4 days postpartum and is characterized by high fever, chills, flashing, abdominal pain, and uterine tenderness. Nonetheless, patients with GAS puerperal sepsis may have an unusual presentation, when fever is absent, and the symptoms and signs can be mild, nonspecific, and not indicative of the severity of infection. This unusual presentation may lead to a delayed diagnosis and increase the risk for severe puerperal sepsis. Therefore, in these cases, a high index of suspicion and prompt early antibiotic and surgical treatment is crucial to saving the parturient's life.